Fluctuation between cigarette smoking and use of electronic nicotine delivery systems: Impact on clozapine concentrations and clinical effect - Montville Daniel J. MD; Lindsey Jaclyn M. MD; Leung Jonathan G. PharmD (American Association of Psychiatric Pharmacists, 2021)
Unlike with smoking cigarettes, electronic nicotine delivery systems do not cause CYP450 1A2 induction as there is a lack of combustion and polycyclic aromatic hydrocarbon production. Changing to the use of an electronic nicotine delivery system from cigarettes can result in the deinduction of CYP450 1A2 and the increase of certain medication serum concentrations, including clozapine. A case is reported in which the switch from smoking to an electronic nicotine delivery system resulted in increased clozapine serum concentration and constipation, necessitating pharmacologic management. The patient ultimately transitioned back to cigarettes, which resulted in the emergence of psychiatric symptoms. An evaluation of longitudinal serum concentrations and clinical correlation is provided. It is important that patients and health care professionals have knowledge not only about the impact of smoking cigarettes on clozapine metabolism, but also the effects of switching to or from an electronic nicotine delivery system.